Joyful Number Talks in Kindergarten - Deanna Marie Pecaski McLennan (University of Windsor, 2020)
This article discusses the use of number talks to engage kindergarten children in regular joyful math opportunities in the classroom. As an educator of four- and five-year-old students in a full day kindergarten (FDK) program in Ontario, Canada, I embrace inquiry-based learning to guide children's activities. Inspired by the childcare centres in Reggio Emilia, Italy, I continually support and scaffold the expressed interests of children in the form of projects. This means that children are engaged in and discover answers to self-directed questions on a regular basis. I have always compared kindergarten to a dance; sometimes I lead and other times I follow.